Simple versus complicated appendicitis - Singh, Mahendra Pal (International Surgery Journal, 2021)
Aim of this study is to understand appendicitis in its various presentations. We encounter patients in different stages of the disease. One end of the spectrum is presenting with simple acute appendicitis while other extreme is represented by serious cases of perforated appendicitis. In between cases with various stages of complications could be seen. Simple appendicitis progresses towards complicated one in its natural course. Rise in intraluminal pressure leads to gangrenous perforation. Expertise of the treating surgeon lies in timely detection and intervention. Desired and favorable results are possible to achieve with judicious use of gastrointestinal surgical techniques by the expert. Present study reviews the literature, different research papers and studies available. My own clinical experience in the understanding of appendicitis and its management has enabled me to shape up the article.